Penerapan Model Project Based Learning terhadap Keterampilan Berpikir Kritis dan Keterampilan Kolaborasi pada Pembelajaran Biologi Kelas XII - Chaidir, Diki Muhamad; Nuriyah, Ai (Undiksha, 2023)
The purpose of this study was to determine the effect of the project-based learning model on critical thinking skills and collaboration skills in biotechnology material in class XII MIPA SMA Negeri 1 Taraju. This study uses a quantitative approach with a quasi-experimental method. The research population was all class XII MIPA, namely 127 students. With the sampling technique that is purposive sampling so that a sample of 64 people is obtained. The instrument consists of test instruments and non-test instruments. The test is in the form of 16 essay questions to measure critical thinking skills. The non-test is in the form of 24 statement items in the form of a questionnaire to measure collaboration skills. The data analysis technique uses the ANOVA test. The results of this study indicate that there is an influence of the project-based learning model on critical thinking skills and collaboration skills indicated by a significance value of less than 0.05, which is equal to 0.00. So, it can be concluded that there is an influence of the project-based learning model on students' critical thinking skills and collaboration skills in biotechnology material in class XII MIPA SMA Negeri 1 Taraju even semester of the 2022/2023 academic year.